Hubungan Pengetahuan Ibu dalam Pemberian ASI Perah (Breast Pumping) dengan Keberhasilan ASI Eksklusif di Puskesmas Lampulo - Ummi Rakida; Fauziah Fauziah; Nurul Sakdah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Exclusive breastfeeding, sometimes known as ASI, is the practice of giving infants only breast milk, along with vitamins, supplements, and prescription medications for illnesses, and no other liquids or solid foods, either directly from the breast or expressed. The purpose of this study was to determine the relationship between maternal awareness of pumping and the effectiveness of exclusive breastfeeding at the Lampulo Community Health Center. This study used a cross-sectional methodology and an analytical quantitative design. 53 breastfeeding mothers constituted the study population. There were 53 respondents in total, and the sampling strategy used the total sampling method. A 20-question survey taken from Desriati Sinaga's 2024 study served as the instrument. The Lampulo Community Health Center in Banda Aceh conducted this study from May 19 to June 25, 2025. The Chi-square test results showed a p-value of 0.001 < 0.05. Based on the research findings, maternal awareness of expressing breast milk is related to the success of exclusive breastfeeding at the Lampulo Community Health Center. These findings are expected to form the basis for more comprehensive instructions for breastfeeding mothers to improve the success of exclusive breastfeeding with expressed breast milk.